Paleomagnetic Recording Efficiency of Sedimentary Magnetic Mineral Inclusions: Implications for Relative Paleointensity Determinations. Issue 7 (22nd July 2019) - Hong, Hoabin; Chang, Liao; Hayashida, Akira; Roberts, Andrew P.; Heslop, David; Paterson, Greig A.; Kodama, Kazuto; Tauxe, Lisa
Abstract: Sedimentary relative paleointensity (RPI) records are often carried by complex magnetic mineral mixtures, including detrital and biogenic magnetic minerals. Recent studies have demonstrated that magnetic inclusions within larger detrital silicate particles can make significant contributions to sedimentary paleomagnetic records. However, little is known about the role such inclusions play in sedimentary paleomagnetic signal recording. We analyzed paleomagnetic and mineral magnetic data for marine sediment core MD01‐2421 from the North Pacific Ocean, offshore of central Japan, to assess how magnetic inclusions and other detrital magnetic minerals record sedimentary paleomagnetic signals. Stratigraphic intervals in which abundant magnetic inclusions dominate the magnetic signal are compared with other intervals to assess quantitatively their contribution to sedimentary RPI signals. The normalized remanence record from core MD01‐2421 does not correlate clearly with global RPI stacks, which we attribute to a demonstrated lower paleomagnetic recording efficiency of magnetic inclusions compared to other detrital magnetic minerals. We also carried out the first laboratory redeposition experiments under controlled Earth‐like magnetic fields for particles with magnetic inclusions using material from core MD01‐2421. Our results confirm that such particles can be aligned by ambient magnetic fields but with a lower magnetic recording efficiency compared to other detrital magnetic minerals, which is consistent with normalized remanence data from core MD01‐2421. Our demonstration of the role of sedimentary magnetic inclusions should have wide applicability for understanding sedimentary paleomagnetic recording. Key Points: Sedimentary intervals rich in detrital magnetic mineral inclusions commonly record biased geomagnetic field intensity minima Redeposition experiments of inclusion‐rich sediments indicate lower recording efficiency compared to inclusion‐poor samples Variable recording efficiency of magnetic assemblages produces a bias that needs to be recognized in relative paleointensity records